Ava and star - "Sykes, Julie" (London; Nosy Crow, 2018)
"Imagine a school where you meet your own unicorn and learn to talk to them! That's what happens for the girls at Sparkle Lake Academy on beautiful Unicorn Island. The girls have an important job to do - they must discover their unicorn's special magic before the annual Starlight Parade. What's more, it looks like some mysterious people want to harm the island and its magic. This year at Sparkle Lake Academy is certainly going to be a big adventure!Isabel and Moonlight are finding it hard to get along. Isabel is impetuous and hasty, and Moonlight is more cautious and (Isabel thinks) dull. But when they go off on a thrilling adventure along the coast of Unicorn Island, the two become firm friends in the face of terrible danger!"--Publisher description
Keywords: English Fiction